CNCP Fractions and in Vitro Rumen Fermentation of Straw Based Total Mixed Rations Supplemented with Leucaena leucocephala Leaves - Rajvaidya, Saurabh; Mohini, Madhu; Sarkar, Srobana; Mondal, Goutam; Pandita, Sujata (Indian Journal of Animal Nutrition, 2018)
An in vitro study was conducted to evaluate the effect of the different ratios of Leucaena (Leucaena leucocephala) leaves (L), wheat straw (W) and concentrate mixture (C) on total gas production, methanogenic potential and other rumen fermentation parameters using in vitro gas production technique. Four total mixedration (TMR) were prepared using dried ground samples of W, C and L: WC (90W: 10C), WCL10 (80W: 10C: 10L), WCL25 (65W: 10C: 25L) and WCL50 (40W: 10C: 50L). For estimation of fermentation parameters, TMR samples (200 mg) were incubated with 30 mL buffered rumen liquor at 39Â±0.5ÂºC for 24 h. As the level of Leucaenaleaves increased in the substrate, total gas production increased (P